Tinjauan Kritis Hak Pekerja Kontrak Dalam Pemutusan Hubungan Kerja Berdasarkan PP No. 35 Tahun 2021 - Arifin Arifin; Muhammad Luthfi Radian; Dhea Gita Imelda (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
The government was formed to protect all Indonesian people, advance public welfare and educate the nation. The Indonesian nation consists of various ethnicities, cultures and languages ​​but is united in diversity. To regulate diverse life, the government makes various policies, both through laws, government regulations, etc. In industrial relations, the government has enacted the Employment Law and Government Regulations that regulate rights and obligations as well as work conditions. The Employment Law currently in effect is Law No. 13 of 2003 concerning Employment and Law No. 6 of 2023 concerning Job Creation. One of the contents of Law No. 13 of 2003 concerning Employment and Law No. 6 of 2023 concerning Job Creation is about the Rights of Contract Workers (PKWT) whose employment relationship ends due to the end of the agreed period or the termination of their employment relationship before the end of the agreed period. As an implementing regulation of the Law, the Government issued Government Regulation No. 35 of 2021 concerning Fixed-Term Employment Agreements, Outsourcing, Working Hours and Rest Hours, and Termination of Employment.